Structural and Functional Brain Asymmetries in Mirror Image People - AlJumah, Nada (Journal of medical and pharmaceutical sciences, 2017)
It is routine for most people to salute their flag by placing their hands on their hearts. However, not every person has this capability because some people are born with a reversed position of the heart as well as other organs in the body. Thus, as for the human brain, separate functions tend to be restricted within the left as well as right hemispheres. Language ability mainly occurs in the left hemisphere. However, there are other unique cases where the structure of the organs appears to be having a different location from how it appears normally. This disorder is called situs inversus abbreviated as SI and it is rare among people Aim: To explore the difference in learning abilities as between SI individuals and normal individuals. Besides, the it also examines factors affecting the learning abilities of the SI individuals. Methods: SI group individuals were compared with the normal individuals to identify the disparity between these two groups. Besides, field data was collected on the views of SI individual in the society to identify the perception regarding their rare condition in the society. Results: 8 of 16 participants were SI positive and they showed low gamma readings in hemispheres of their brains. Language ability is controlled by left hemisphere in all the participants. Conclusion: Despite SI individuals showing a different structural brain as well as other organ composition in the body, they have equal learning abilities. The disparity emanates from other social factors affecting their incorporation in the society.